De cómo la pugna se torna cooperación: alrededor de una noción de Poder en la propuesta de John Rawls - Salas Murillo, Bértold (2014)
This paper examines the meaning of power and conflict in John Rawls. The paper shows that even though Rawls’ acknowledges power relations and conflict, he fails in adjudicating individuals and social groups some traits that overlook motives beyond reason and good manners. Rawls’ proposal aims at liberating political pragmatics from passion and fanaticism; he also attempts to establish the procedures to manage the differences among comprehensive doctrines, but neglects the asymmetries that are inherent to the dynamics of power.